2004
DOI: 10.1128/iai.72.6.3129-3137.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Limits Local and Body Cavity Inflammation during Infection with Muscle-StageTrichinella spiralis

Abstract: The aim of this study was to characterize cellular responses to muscle-stage Trichinella spiralis. From its intracellular habitat in muscle, T. spiralis secretes potent glycoprotein antigens that elicit a strong systemic host immune response. Despite the magnitude and prolonged nature of this response, nurse cells are rarely destroyed by infiltrating cells. We tested the hypothesis that the anti-inflammatory cytokine interleukin-10 (IL-10) moderates cellular responses to muscle-stage parasites. Trichinella lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 51 publications
2
60
0
Order By: Relevance
“…Other studies showed higher IFN-γ level and lower IL-5 level after 15 dpi in BALB/c mice infected with T. spiralis, what additionally confirms the role of Th-1 response (Dvorožňáková et al, 2005). Cytotoxic activation of macrophages was also suggested by Beiting et al (2004) who demonstrated IL-10 participation in local inflammatory response suppression in the neighborhood of nurse-cell as well as studies where revealed strong growth of antioxidant enzymes (ex. superoxide dismutase (SOD)) level in blood and muscles (Derda & Hadaś, 2000;Derda et al, 2004).…”
Section: Discussionsupporting
confidence: 48%
“…Other studies showed higher IFN-γ level and lower IL-5 level after 15 dpi in BALB/c mice infected with T. spiralis, what additionally confirms the role of Th-1 response (Dvorožňáková et al, 2005). Cytotoxic activation of macrophages was also suggested by Beiting et al (2004) who demonstrated IL-10 participation in local inflammatory response suppression in the neighborhood of nurse-cell as well as studies where revealed strong growth of antioxidant enzymes (ex. superoxide dismutase (SOD)) level in blood and muscles (Derda & Hadaś, 2000;Derda et al, 2004).…”
Section: Discussionsupporting
confidence: 48%
“…Although we did not detect the obvious cellular changes in the intestines of rats infected by this route, it is possible for stimulation of mucosal associated lymphoid tissue in one site to affect another site. An additional source of cellular mediators may derive from the body cavities in which cellular expansion during muscle infection has been documented in mice (52,53). Recirculation of cells from the cavities to the intestinal tract, or direct effects of peritoneal responses on the gut have been shown to be a part of the body's defense against intestinal pathogens (54).…”
Section: Discussionmentioning
confidence: 99%
“…Also during the muscle phase of the light infection there was an increased occurrence of CD4 cells in comparison with the heavy infection. The increase of both T cell populations during the muscle phase of trichinellosis can be associated with larval development in nurse cells, which are surrounded by macrophages, CD8+ and CD4+ T lymphocytes and B lymphocytes (Beiting et al, 2004). Cytokines synthetized primarily by T helper cells play a dominant role in orchestrating both anti-parasite responses and pathology in many helminth infections including trichinellosis (Finkelman et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae survive in nurse cells in close association with macrophages, CD8+ and CD4+ T lymphocytes, and B lymphocytes. B lymphocytes secreting antibodies, particularly IgG and IgE, may lead to an effective antibodydependent cell mediated cytotoxic reaction against newborn larvae (Beiting et al, 2004). Potential differences in a development of the host immune HELMINTHOLOGIA, 50, 4: 244 -253, 2013 Differences in cellular immune responses of mice BALB/c to low and high infective doses of Trichinella spiralis 245 response to different infective doses of Trichinella and host-parasite interactions are rarely studied.…”
Section: Introductionmentioning
confidence: 99%